Offshore wind power potential analysis for different wind turbines in the Mediterranean Region, 1959-2020 - Gormus, Tahsin; Aydogan, Burak; Ayat, Berna (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
We evaluated spatiotemporal characteristics of the wind power density (WPD) in the Mediterranean and the Black Sea. An hourly wind speed data from ERA5 of ECMWF is used covering 62 years between 1959 and 2020. Spatial distributions of WPD at 100 m altitude at monthly, yearly, and seasonal timescales are revealed. The average WPD in the study area is 373 W/m(2), where the spatial maximums in the 62-year average map reach up to 1116 W/m(2). The spatial distribution of yearly mean WPD considering 13 sub-basins revealed that the two most prominent regions are the Gulf of Lion and the Aegean Sea. The diurnal variation of WPD showed over +/- 10 % variability within the considered sub-basins. Five commercial turbines are selected to investigate their performance in the study area. The capacity factors, and operational and rated power time percentages are spatially mapped. The variability in the WPD is investigated using several indicators of yearly variability index, intra-annual variability index, coefficient of variation, robust coefficient of variation, inter-quartile range, and inter-quartile ratio. The long-term trend in the monthly-mean values is investigated and it is revealed that the statistically significant downward trends manifest themselves in the Levantine Basin, Ligurian-Provencal Basin, Balearic Sea, and the Alboran Sea. The capacity factors of five widely used wind turbines are computed in the study area using both yearly and seasonal timescales.
Keywords: Wind power potential; Temporal variability; Trend analysis; Mediterranean; Black Sea; Wind turbine; CLIMATE-CHANGE; BLACK; MODELS; Thermodynamics; Energy & Fuels; Mechanics